FACTORS THAT INFLUENCE ON THE DEVELOPMENT OF PAID AGRO-TOURISM IN THE MARKET TRANSMISSION VILLAGE - Adelina Lubis; Indah Apriliya; Kartika Anggraeni Simbolon; Nurul Wardani Lubis (Jurnal Ekonomi, 2023)
Pasar Melintang Village has a stretch of rice fields that have not been widely developed into an agro-tourism destination in North Sumatra. The purpose of this study was to examine what factors influence the development of agro-tourism in Pasar Melintang Village in Deli Serdang. The respondents of this study amounted to sixty-three people who live in Lubuk Pakam District and have visited the location, the sampling technique used is a combination of purposive and accidental sampling with the following criteria: 1) minimum age 17 years, 2) minimum high school education, 3) have visited rice field tourism sites. The analysis technique uses Confirmatory Factor Analysis with eleven-factor variables. Of the eleven variables, three factors were formed: attractiveness, management, and community participation